Financial Development and Poverty Reduction in South Africa - Bopape, Gertrude (Faculty of Commerce, 2023)
South Africa has high levels of financial development yet experiences significant and persistently high levels of poverty. Intrinsically, this research examines the relationship between financial development and the reduction of poverty in South Africa. The research employed the Vector Error Correction Model (VECM) technique based on annual data from 1980 to 2019. Using the financial depth indicator as a measure of financial development and household final consumption expenditure per capita growth, income per capita and infant mortality rate as proxies for poverty, three models were developed. The results show that in the long run, financial development – as measured by the financial depth indicator – has a positive impact on poverty reduction, yet the findings are insignificant. This is consistent across all measures of poverty. In the short run, the growth in Gross Domestic Product (GDP) was found to be beneficial in reducing poverty, but only when household final consumption expenditure per capita growth and income per capita growth were used as proxies for poverty. GDP growth has also been found to Granger-cause poverty reduction when household final consumption expenditure per capita growth and income per capita growth were used. The study recommends designing policies that will ensure that financial sector development translates to impact at grassroots level. Furthermore, a recommendation is made for further studies in effective measurements of poverty, positing that measuring poverty on an annual basis is key in the fight to reducing the incidence of poverty in South Africa.